2018
DOI: 10.1002/jcb.27291
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of exosome‐encapsulated miR‐548c‐5p is associated with poor prognosis in colorectal cancer

Abstract: The role of circulating exosomal microRNAs (miRNAs) in colorectal cancer (CRC) has drawn more and more attention during the past few years. Previously, we have identified several specific miRNAs in serum exosomes as potential CRC biomarkers. However, little is known about the association between exosome-encapsulated miR-548c-5p and outcomes of patients with CRC. In the current study, the expression of serum exosomal miR-548c-5p was investigated by quantitative real-time polymerase chain reaction. Its correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 23 publications
0
51
0
Order By: Relevance
“…Liu et al likewise found elevated miR-486 levels in the serum EVs of CRC patients of all stages [74]. Downregulation of serum EV miR-548c was also reported by Peng and colleagues in 108 CRC patients (including 25 stage I and 21 stage II patients) and was associated with shorter survival and liver metastases [82]. However, in this study, miR-548c was demonstrated to have a 1.59-fold decrease and miR-486 was shown to have a 1.61-fold increase.…”
Section: Diagnostic Ev-mirnas In Plasma and Serummentioning
confidence: 54%
See 1 more Smart Citation
“…Liu et al likewise found elevated miR-486 levels in the serum EVs of CRC patients of all stages [74]. Downregulation of serum EV miR-548c was also reported by Peng and colleagues in 108 CRC patients (including 25 stage I and 21 stage II patients) and was associated with shorter survival and liver metastases [82]. However, in this study, miR-548c was demonstrated to have a 1.59-fold decrease and miR-486 was shown to have a 1.61-fold increase.…”
Section: Diagnostic Ev-mirnas In Plasma and Serummentioning
confidence: 54%
“…This has possible efficiency benefits over a method such as UC, with potential of ease of scalability and automation. Other methods of EV isolation include precipitation and filtration that were also in a number of studies [74,[80][81][82]118]. Differences in EV isolation methods, including UC, precipitation, and SEC, have demonstrated significant variance in the properties of the isolated vesicles, the total miRNA yield, as well as the EV-specific miRNA levels when analysing the same samples [119,120].…”
Section: Challenges In Using Mirnas As Diagnostic Biomarkersmentioning
confidence: 99%
“…Moreover, recent evidence has suggested that liver pre-metastatic niche could be promoted by exosomal miR-21 of CRC cells, through the miR-21-TLR7-IL6 axis [116]. Significantly increased levels of serum exosomal miR-6803-5p [117] and decreased levels of miR-548c-5p have been recently associated with poor survival and liver metastasis of CRC patients [118]. However, the molecular mechanisms by which both miR-6803-5p and miR-548c-5p influence CRC metastasis remain largely unknown.…”
Section: The Role Of Mirnas -Tex In Sustaining the Crc Liver Metastasismentioning
confidence: 99%
“…miRNAs contribute to both stem cell homeostasis in normal development and to cell fate decisions in CRC [13]. Clinical studies have also confirmed their utility as molecular diagnostic and prognostic biomarkers for a wide range of human diseases, including CRC [14][15][16]. Some evidences suggest that age, gender and other parameters could affect miRNA expression.…”
Section: Introductionmentioning
confidence: 99%